KEMAMPUAN MAHASISWA DALAM MENGEMBANGKAN ALAT PERMAINAN EDUKATIF BERBASIS PERKEMBANGAN ANAK: PERAN KELOMPOK BELAJAR APE - Syarfina, Syarfina (A?f?luna: Journal of Islamic Early Childhood Education, 2020)
Early childhood educators are not only expected to be professional in teaching but also in developing educational toys (ET). As a prospective Early Childhood Education (ECE) teacher, students who are taking lectures in the ECE program should have an early opportunity to increase their potential in developing ET. However, the ability of students to develop ET is still limited, and the design does not cover the entire content of child development. This study aims to recognize to what extent students' ability of Early Childhood Islamic Education programs can improve in developing educational toys based on all aspects of child development through participating in a study group. This research is a qualitative approach with 25 participants of the study group Data collection is conducted by observation, documentation, and interviews. The results showed that; (1) the ability of students in developing ET has emphasized all aspects of child development, (2) APE study groups can improve students' abilities and motivation in developing ET. The effectiveness of ET, which has been become products, can be identified in further research